Image analysis on wire bonding - Mohd. Noor, Norliza (Universiti Teknologi Malaysia, 2005)
A software was created to calculate the intermetallic area in the MATLAB software environment. The software able to give an exact percentage of the intermetallic area using 2 methods that is %1M - based on normal-normal mixture modeling and gammagamma mixture modeling. The software also gives a compactness number where a low value means good compact of the intermetallic area and high value means bad. Compactness will give user an indication on the quality of the wire bonding.